The Impact of E-schoolbag on Students’ Information Literacy Proficiency- A Case Study of M District in Shanghai, China (International Conference on Computers in Education, 2016)
As one of the core competitiveness in the 21st century, information literacy has attracted more and more attention of the educators all over the world. However, limited empirical research focused factors that affect students’ information literacy proficiency in educational practices. This paper reported a case study of a three-year e-schoolbag project in M District of Shanghai and explored the impacts of the e-schoolbag learning on students' information literacy proficiency. We conducted a questionnaire on students’ applications of e-school bag and information literacy proficiency, and received 4002 valid responses. The independent-sample T-test results showed that the use of e-schoolbag had a positive impact on the students' information literacy proficiency, and among the students who used the eschoolbag, there was a significant difference between male and female students on information literacy proficiency.